An African Growth Miracle? Or: What do Asset Indices Tell Us about Trends in Economic Performance? - Kenneth Harttgen; Stephan Klasen; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
Using changes in the possession of household assets over the past 20 years, several recent papers have argued that economic performance in Arica was substantially better than suggested by national income data and income poverty statistics, who suffer from well-known weaknesses. We scrutinize these claims and first argue that trends in assets provide biased proxies for trends in incomes or consumption. In particular we show that the relationship between growth in assets and growth in incomes or consumption is extremely weak; instead, we find evidence of asset drift using macro and micro data, which is consistent with the claims we make about possible biases in the use of asset indices. As a result, we find no evidence supporting the claim of an African growth miracle that extends beyond what has been reported in GDP/capita and consumption figures.
Keywords: O47; O11; O12; 330; Asset index; GDP growth; Africa